2019
DOI: 10.3390/catal9060510
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chemical Modifications of Polyhydroxyalkanoate-Derived Fatty Acids on Their Antimicrobial Properties

Abstract: Sugar esters are bioactive compounds derived from renewable resources. They consist of a sugar moiety with attached non-polar part – usually a fatty acid. These compounds find uses in cosmetic, food and pharmaceutical industries as surfactants due to their physicochemical and antimicrobial activities. In this study we have produced fatty acids for sugar ester synthesis from bacterially derived polyesters, namely polyhydroxyalkanoates (PHAs). We have developed methodology to decorate PHA monomers with a fluorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Being precursors of prostaglandins, lipoxin (peak 62; m/z 353.2317, C 20 H 33 O 5 + ), oxolipoxin (peak 66; m/z 351.2159, C 20 H 31 O 5 + ), linolenic acid (peak 89; m/z 279.2332, C 18 H 31 O 2 + ) and its methyl ester (peak 98; m/z 293.2487, C 19 H 33 O 2 + ) exhibited anti-inflammatory effects [ 56 ]. Moreover, some hydroxylated fatty acids were present as major peaks and showed additional water molecule loss, aside from their cytotoxic and antimicrobial capacity [ 57 ]. For example, hydroxylinolenic acid (293.215, C 18 H 29 O 3 − ) and hydroxyolinoleic acid (295.2303, C 18 H 31 O 3 − ) revealed 2 amu mass differences attributed to the extra double bond with fragment ions at m/z 275 and 277, respectively due to the subsequent loss of one water molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Being precursors of prostaglandins, lipoxin (peak 62; m/z 353.2317, C 20 H 33 O 5 + ), oxolipoxin (peak 66; m/z 351.2159, C 20 H 31 O 5 + ), linolenic acid (peak 89; m/z 279.2332, C 18 H 31 O 2 + ) and its methyl ester (peak 98; m/z 293.2487, C 19 H 33 O 2 + ) exhibited anti-inflammatory effects [ 56 ]. Moreover, some hydroxylated fatty acids were present as major peaks and showed additional water molecule loss, aside from their cytotoxic and antimicrobial capacity [ 57 ]. For example, hydroxylinolenic acid (293.215, C 18 H 29 O 3 − ) and hydroxyolinoleic acid (295.2303, C 18 H 31 O 3 − ) revealed 2 amu mass differences attributed to the extra double bond with fragment ions at m/z 275 and 277, respectively due to the subsequent loss of one water molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The hydroxylated acid methyl esters were analyzed by gas chromatography. Modification of the resultant methyl esters of monomers was conducted as described previously [29]. The obtained monomers were converted into their acidic forms using Candida antarctica lipase B under aqueous conditions to obtain sodium salts.…”
Section: Preparation Of Unmodified and Modified Polyhydroxynonanoate Monomersmentioning
confidence: 99%
“…PHAs can serve as material for manufacturing of nontoxic implants and other medical devices. They also are often used as media for drug delivery upon implantation [28][29][30]. To date, more than 150 different (R)-3-hydroxyacids have been reported, thus creating endless possibilities for further modifications [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identities of quinic acid, tannic acid, apigenin and gallic FULL PAPER Phenolic compounds with less-complex structures possess antimicrobial activities and play essential roles in killing antibiotic-resistant pathogens. Snoch et al (2019) suggested phenylvaleric acid, which is one of the phenolic acids, has a strong antibacterial effect towards S. aureus, C. albicans and E. coli. Quinic acid also has strong antibacterial properties where it can easily attack the intracellular cell of bacteria.…”
Section: Presence Of Phenolic Constituent In Sugarcane Molasses Extractmentioning
confidence: 99%